The Playful Entrepreneur : How to Adapt and Thrive in Uncertain Times - Dodgson, Mark, (Yale University Press, 2018)
A compelling account of how incorporating play into work can help us overcome the uncertainty and turbulence that surrounds work How can we learn to deal with uncertainty at work? The answer, as Dodgson and Gann eloquently portray in this pathfinding book, is to learn from the adaptive behaviors of entrepreneurs. Play, the authors show, is a crucial component of this. It encourages exploration, experimentation, and curiosity while it also challenges established practices and orthodoxies. It facilitates change in people and organizations. Drawing on in-depth interviews with entrepreneurs and innovators, this book explains why we should incorporate play into work, what play looks like, and how to encourage playfulness in individuals and organizations. Dodgson and Gann identify four key behaviors that endorse, encourage, and guide play: grace, craft, fortitude, and ambition, and provide a blueprint for an alternative way of working that fosters resilience and encourages innovation and growth in difficult times.